On method - Kortlandt, Frederik (Baltistica, 2017)
The basis of linguistic reconstruction is the comparative method, which starts from the assumption that there is “a stronger affinity, both in the roots of verbs and in the forms of grammar, than could possibly have been produced by accident”, implying the existence of a common source (thus Sir William Jones in 1786). It follows that there must be a possible sequence of developments from the reconstructed system to the attested data. These developments must have been either phonetically regular or analogical. The latter type of change requires a model and a motivation. A theory which does not account for the data in terms of sound laws and well-motivated analogical changes is not a linguistic reconstruction but philosophical speculation. The pre-laryngealist idea that any Proto-Indo-European long vowel became acute in Balto-Slavic is a typical example of philosophical speculation contradicted by the comparative evidence. Other examples are spontaneous glottalization (Jasanoff’s “acute assignment”, unattested anywhere in the world), Jasanoff’s trimoraic long vowels, Eichner’s law, Osthoff’s law, and Szemerényi’s law, which is an instance of circular reasoning. The Balto-Slavic acute continues the Proto-Indo-European laryngeals and the glottalic feature of the traditional Proto-Indo-European “unaspirated voiced” obstruents (Winter’s law). My reconstruction of Proto-Indo-European glottalic obstruents is based on direct evidence from Indo-Iranian, Armenian, Baltic and Germanic and indirect evidence from Indo-Iranian, Greek, Latin and Slavic.